Prospective analysis of post-operative pain management in elective laparotomies in a tertiary care centre - T., Nithya; Rajagopalan, S. (International Surgery Journal, 2021)
Background: The study was conducted to record the drug used for postoperative pain in elective laparotomies and to determine the effectiveness of multimodal analgesics used. Methods: A prospective observational study for a period of 15 months from March 2019 to May 2020 in 140 patients who underwent elective laparotomies from the department of general surgery Rajarajeswari medical college and hospital (tertiary care center). Results: A total of 140 patients were included among which 58 (41.4%) were female and 82 (58.6%) were male patients. The 20 different types of surgeries were recorded. In our study the most common surgery performed was open appendectomy followed by open cholecystectomy. Most common mode of analgesia used was combined analgesia. Opioids, NSAIDS (non-steroidal anti-inflammatory drugs), epidural and transdermal patch was used. NRS (numerical rating scale) score was recorded for all 140 patients on postoperative days 1, 2 and 3. Conclusions: Combined analgesia was better mode of pain management method than a single analgesic. Due to different multimodal analgesics used in different institutions patients experienced different degrees of pain, hence we need a standard protocol for a best pain management method.